2013
DOI: 10.1088/0067-0049/207/1/10
|View full text |Cite
|
Sign up to set email alerts
|

THE HUBBLE SPACE TELESCOPE TREASURY PROGRAM ON THE ORION NEBULA CLUSTER ,

Abstract: The Hubble Space Telescope (HST) Treasury Program on the Orion Nebula Cluster has used 104 orbits of HST time to image the Great Orion Nebula region with the Advanced Camera for Surveys (ACS), the Wide-Field/Planetary Camera 2 (WFPC2) and the Near Infrared Camera and Multi Object Spectrograph (NICMOS) instruments in 11 filters ranging from the U-band to the H-band equivalent of HST. The program has been intended to perform the definitive study of the stellar component of the ONC at visible wavelengths, address… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
88
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(90 citation statements)
references
References 73 publications
2
88
0
Order By: Relevance
“…We therefore have to assume that the zeropoints applied by Da Rio et al include an unknown component that causes a shift of the central effective wavelength of the red filters, but less of a shift for the green filter 8 . Since the Orion Nebula is too bright for SDSS stellar photometry to work and all four stars are marked as saturated in the HST ACS catalog of Robberto et al (2013), we cannot cross-check our reconstructed magnitudes with a betterstudied photometric system.…”
Section: Magnitudes and Colorsmentioning
confidence: 99%
“…We therefore have to assume that the zeropoints applied by Da Rio et al include an unknown component that causes a shift of the central effective wavelength of the red filters, but less of a shift for the green filter 8 . Since the Orion Nebula is too bright for SDSS stellar photometry to work and all four stars are marked as saturated in the HST ACS catalog of Robberto et al (2013), we cannot cross-check our reconstructed magnitudes with a betterstudied photometric system.…”
Section: Magnitudes and Colorsmentioning
confidence: 99%
“…(J2000.0) = −05°23′52 99 is located southwest of θ 1 Ori C. The projected distance between them is about 0.11 pc. In Figure 1, we show the HST ACS color-composite image of Proplyd 133-353 using the HST images from Robberto et al (2013). The tail can be clearly seen in the HST image in the F658N band (green emission) and extends out to 190 au.…”
Section: Proplyd 133-353mentioning
confidence: 99%
“…The tail can be clearly seen in the HST image in the F658N band (green emission) and extends out to 190 au. We visually inspected the HST images of the object in different bands from Robberto et al (2013) and found that the tail can also be clearly detected in the F435W band for ACS/WFC, and the F336W and F656N bands for WFPC2, which could be due to the tail showing strong Balmer emission lines, e.g., Hα (F658N), Hγ (F435W), and Balmer continuum emission (F336W).…”
Section: Proplyd 133-353mentioning
confidence: 99%
“…Maddalena et al 1986;Blaauw 1991;Brown et al 1995;Wilson et al 2005;Bally 2008;Lombardi et al 2011), is probably the most often studied molecular-cloud complex (see Bally 2008;Muench et al 2008;Robberto et al 2013;Schneider et al 2013). It contains the nearest massive star-forming cluster to Earth, the Trapezium cluster (e.g.…”
Section: Introductionmentioning
confidence: 99%